A questão da norma culta e o ensino de língua padrão no curso de Letras: um estudo de caso - Clemeson Campos da Cunha (2008)
In this paper, we aim to describe and to analyze the Portuguese Language teachers formation process, nowadays, taking as base information supplied by teachers of institutions with degree in Letters course and graduates in process of conclusion of this course. In this perspective, we investigate the aspects that involve the teaching-learning of mother language in the Letters course, specially the standard language and standard grammar, as well as their implications in the teaching process after university. Initially, we present a general view about the educational formation, and the objectives intended inthis paper. Afterwards, we present the theoretical bases that have as base the presuppositions of the socio-discursive interaction of Bronckart (1999) and the sociocognitive-interactional conceptions of Bakhtin (1995). After we trace the teachers profile and the Portuguese Language teachers function while mediator in the teachinglearningprocesses, we present the used methodology and the analysis of the data. The results retake the scope of the process of educational formation, proving the hypothesis that an effective attention has not been given in the aspects that concern the teachinglearning of the Portuguese Language in the Letter course, specially the standard grammar,factor that is interfering in the educational construction of the recently-formed professional.